1985
DOI: 10.1002/bit.260270613
|View full text |Cite
|
Sign up to set email alerts
|

Application of L‐(+)‐Lactate electrode for clinical analysis and monitoring of tissue culture medium

Abstract: L-(+)-Lactate oxidase (EC 1.1.3.2) was immobilized onto the porous side of a cellulose acetate membrane with asymmetric structure which has selective permeability to hydrogen peroxide. The lactate electrode was constructed by combination of a hydrogen peroxide electrode with the immobilized enzyme membrane. Properties of the enzyme membrane and characteristics of the lactate electrode were clarified for the determination of L-(+)-lactic acid. The lactate electrode responded linearly to L-(+)-lactic acid over t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

1991
1991
2012
2012

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(8 citation statements)
references
References 10 publications
(1 reference statement)
0
8
0
Order By: Relevance
“…3 for the latter. The pH optimum of soluble LOD has been reported to be around 7 [27,28]. In contrast, the pH to obtain maximal fluorescence signal intensity of the bienzyme optode was even higher than that of the HRP sensor, i.e.…”
Section: Lactate Sensormentioning
confidence: 91%
“…3 for the latter. The pH optimum of soluble LOD has been reported to be around 7 [27,28]. In contrast, the pH to obtain maximal fluorescence signal intensity of the bienzyme optode was even higher than that of the HRP sensor, i.e.…”
Section: Lactate Sensormentioning
confidence: 91%
“…In the HER-100 (Omron Tateisi, Japan) an asymmetric cellulose acetate membrane is used, bearing LOD covalently bound by y-aminopropyltriethoxysilane and cross-linked with glutaraldehyde [371]. The membrane is highly selective for hydrogen peroxide.…”
Section: (14-23)mentioning
confidence: 99%
“…Process control in human and animal cell cultures is very important because the required nutrients, eg, fetal calf serum, are extremly expensive [416]. For optimization of cell culture, the HER-100 lactate analyzer (Omron Tateisi, Japan) has been used together with a glucose electrode for lactate and glucose analysis in the growth medium of human melanoma cells [417]. Investigation of the process over 7 d showed that, as a result of glycolysis, with increasing cell number the concentration of glucose decreased and that .of lactate increased.…”
Section: Food Analysis Process Control and Environmental Monitoringmentioning
confidence: 99%
“…The great advantage of immobilized enzymes is that they have very high stabilities as compared with native enzymes. Many techniques of immobilization are available for industrial appli-cations using different matrices [11][12][13][14][15]. Rothe and Aurich [16] proposed particles covalently coated with a phospholipid bilayer coated in organic colloids.…”
Section: Introductionmentioning
confidence: 99%